Numerical investigations of convective phenomena of oil impingement on end-windings - Connor, P.H.; La Rocca1, A.; Xu, Z.; Eastwick, C.N.; Pickering, S.J.; Gerada, C. (2018)
A novel experimental rig for analysing intensive liquid cooling of highly power-dense electrical machine components has been developed. Coupled fluid flow and heat transfer has been modelled, using computational fluid dynamics (CFD), to inform the design of a purpose-built enclosure for optimising the design of submerged oil jet cooling approaches for electrical machine stators. The detailed modelling methodology presented in this work demonstrates the value in utilising CFD as a design tool for oil-cooled electrical machines. The predicted performance of the final test enclosure design is presented, as well as examples of the sensitivity studies which helped to develop the design. The sensitivity of jet flow on resulting heat transfer coefficients has been calculated, whilst ensuring parasitic pressure losses are minimised. The CFD modelling will be retrospectively validated using experimental measurements from the test enclosure.